European yearbook on human rights 2022 / edited by Philip Czech, Lisa Heschl, Karin Lukas, Manfred Nowak, Gerd Oberleitner. - Czech, Philip; Heschl, Lisa; Lukas, Karin; Nowak, Manfred, 1950-; Oberleitner, Gerd, 1967- (Intersentia, 2023)
The 'European Yearbook on Human Rights' brings together renowned scholars, emerging voices and practitioners, comprising contributions which engage with some of the most important human rights issues and developments in Europe. The Yearbook helps to better understand the rich landscape of the European regional human rights system and is intended to stimulate discussions, critical thinking and further research in this field.